Inisiasi Kemampuan Berwirausaha melalui Pengenalan E-Commerce bagi Anak Panti Asuhan Yatim Muhammadiyah Cabang Blimbing Sukoharjo - Mohtar Yunianto; Budi Purnama; Kusumandari Kusumandari; Utari Utari (Jurnal Pengabdian Pada Masyarakat, 2019)
INITIATING ENTREPRENEURIAL SKILLS THROUGH THE INTRODUCTION OF E-COMMERCE FOR ORPHANS OF THE MUHAMMADIYAH ORPHANAGE IN BLIMBING SUKOHARJO. Efforts to improve skills and the cultivation of entrepreneurial spirit have been carried out at the Orphanage PKU Muhammadiyah Cabang Blimbing. This institution is home to 20 orphans located in Wonorejo, Polokarto, Sukoharjo. Wonorejo village is a convection village where most of the population work as convection producers, which in the sale of their clothes still use conventional methods, which are sold in stores and in markets. The pattern of mutually beneficial cooperation between convection entrepreneurs and orphans is initiated by technopreneurship activities namely by selling convection through online stores.